2021
DOI: 10.3390/medicina57030256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Length of Hospital Stay in a Sample of Psychogeriatric Patients Referred to Consultation Liaison Psychiatric Unit

Abstract: Background and objectives: There has been a recent increase in older patients admitted to general hospitals. A significant percentage of hospitalized older patients are ≥75 years old, which differ from the patients aged 65 to 74 years old in terms of functional status at patient discharge. This study aims to compare sociodemographic, clinical features, and factors associated with length of hospital stay in youngest-old and oldest-old populations of inpatients referred to the consultation liaison psychiatry uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…However, two recent studies also focused on geriatric inpatients who were referred to psychiatric consultation. 5,13 Similar to these investigations, delirium, dementia, and depression were identified as the most common psychiatric diagnoses in our study. Furthermore, in terms of age, sex, and somatic comorbidities, our study population showed great similarities with those from previous analyses that focused on geriatric psychiatric inpatients 11,17 Frequency and characteristics of PIM prescriptions have been quite extensively studied in both inpatient and outpatient settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, two recent studies also focused on geriatric inpatients who were referred to psychiatric consultation. 5,13 Similar to these investigations, delirium, dementia, and depression were identified as the most common psychiatric diagnoses in our study. Furthermore, in terms of age, sex, and somatic comorbidities, our study population showed great similarities with those from previous analyses that focused on geriatric psychiatric inpatients 11,17 Frequency and characteristics of PIM prescriptions have been quite extensively studied in both inpatient and outpatient settings.…”
Section: Discussionsupporting
confidence: 88%
“…11 Previous studies showed that pharmacological recommendations are made in up to 50 % of psychiatric consultations. 12,13 Particularly in the Emergency Department (ED), critically ill geriatric patients with acute psychiatric disorders are often treated with psychotropic drugs that display an extensive side-effect profile. 14 This study sought to assess medication safety of geriatric patients in the context of psychiatric consultation service in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed this variance to the higher prevalence of neurocognitive disorders in patients 75 years and older, thus leading to shorter time to referrals for CLP services, as a result of which early and timely management and evaluation takes place and therefore, reduced LOS at the hospital. Furthermore, the main implication from the results was the increase in time to referral or a delay in CLP services was associated with an in LOS, wherein for every 10% increase in time to referral to CLP service, the LOS increased by 5.7% (8).…”
Section: Discussionmentioning
confidence: 89%
“…Nonetheless, patients undergoing CLP referrals were associated with reduced number of readmissions in the 180-day-period after the first discharge. ( 16) Most importantly, patients who have been referred to CLP services have an overall improved quality of life, improved social functioning and return to daily activities and society (8,13). More prospective, comparative studies with larger study samples should be conducted to achieve more precise results.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the abstract noted the addition of a geriatric specialist to weekly multidisciplinary team meetings within a specialist old age psychiatry consultation-liaison service resulted in reduced polypharmacy, a 58% reduction in hospital transfers and a 90% reduction in specialty referrals. 65 In their retrospective audit study (Level IV), Barra et al 66 reported that every 10% increase in time from admission to referral to a general (i.e. not old age specialist) psychiatric consultation-liaison service was associated with a 5.7% longer hospital stay.…”
Section: Service Features Associated With Effectivenessmentioning
confidence: 99%